Epithelial-mesenchymal transition induced by SARS-CoV-2 required transcriptional upregulation of Snail - Lai, Yun-Ju (Am J Cancer Res, 2021)
The engagement of human angiotensin-converting enzyme 2 (hACE2) and SARS-CoV-2 spike protein facilitate virus spread. Thus far, ACE2 and TMPRSS2 expression is correlated with the epithelial-mesenchymal transition (EMT) gene signature in lung cancer. However, the mechanism for SARS-CoV-2-induced EMT has not been thoroughly explored. Here, we showed that SARS-CoV-2 induces EMT phenotypic change and stemness in breast cancer cell model and subsequently identified Snail as a modulator for this regulation. The in-depth analysis identifies the spike protein (S), but not envelope (E), nucleocapsid (N), or membrane protein (M), of SARS-CoV-2 induces EMT marker changes. Suppression of Snail expression in these cells abrogates S protein-induced invasion, migration, stemness, and lung metastasis, suggesting that Snail is required for SARS-CoV-2-mediated aggressive phenotype in cancer. This study reveals an important oncogenic role of SARS-CoV-2 in triggering breast cancer metastasis through Snail upregulation.